Characterization of Brain Iron Deposition Pattern and Its Association With Genetic Risk Factor in Alzheimer’s Disease Using Susceptibility-Weighted Imaging - You, Peiting; Li, Xiang; Wang, Zhijiang; Wang, Huali; Dong, Bin; Li, Quanzheng (Frontiers in Human Neuroscience, 2021)
The presence of iron is an important factor for normal brain functions, while excessive deposition of iron may impair normal cognitive function in the brain and lead to Alzheimer's disease (AD). Magnetic resonance imaging (MRI) has been widely applied to characterize brain structural and functional changes caused by AD. However, the effectiveness of using susceptibility-weighted imaging (SWI) for the analysis of brain iron deposition is still unclear, especially within the context of early AD diagnosis. Thus, in this study, we aim to explore the relationship between brain iron deposition measured by SWI with the progression of AD using various feature selection and classification methods. The proposed model was evaluated on a 69-subjects SWI imaging dataset consisting of 24 AD patients, 21 mild cognitive impairment patients (MCI), and 24 normal controls (NC). The identified AD progression-related regions were then compared with the regions reported from previous genetic association studies, and we observed considerable overlap between these two. Further, we have identified a new potential AD-related gene (MEF2C) closely related to the interaction between iron deposition and AD progression in the brain.